RESTORATIVE JUSTICE AS A MODEL FOR CRIMINAL JUSTICE REFORM IN INDONESIA - Denny Latumaerissa (Penelitian dan Pengembangan Ilmu, 2025)
The criminal justice system in Indonesia has long been dominated by a retributive approach that emphasizes punishment as a form of justice. This approach often fails to meet the needs of perpetrator rehabilitation and victim recovery, leading to criticism of its effectiveness. This study aims to evaluate the effectiveness of restorative justice as an alternative in criminal justice system reform in Indonesia, focusing on its impact on victim satisfaction and reducing recidivism rates. This study uses a Systematic Literature Review (SLR) approach to identify, assess, and synthesize findings from 51 relevant articles. Data collected from the Scopus, Web of Science databases were analyzed using thematic analysis techniques. The findings indicate that the implementation of restorative justice can increase victim satisfaction and reduce recidivism rates, as well as strengthen community involvement in the justice process. This study confirms that restorative justice has significant potential to improve the criminal justice system in Indonesia, with important implications for the development of policies that are more inclusive and responsive to the needs of all parties involved.